Prevalence and Associated factors Of Temporomandibular Joint Dysfunction among Young Adults in Karachi - Hamza Ahmed, Samreen Yasmeen, Farhan Ishaque, Anum Naz, Fazila Khan, Samreen Iqbal (Journal of Rawalpindi Medical College, 2021)
ABSTRACT Objective: The objective of the study was to determine the prevalence and associated factors for temporomandibular joint dysfunction among young adult in Karachi. Material and Methods: A cross-sectional study was carried out in (n=383) subjects with (n=165) males and (n=218) females aged between 18–30 years. The subjects were requested to answer Fonseca’s questionnaires, consisted on ten questions. The collected data sets were analyzed statistically through using the SPSS version 22. Result: A total (n=383) participants, the prevalence of TMD is 66.6%. The participant with TMD (66.6%) show 54.0% mild TMD, 12.0% moderate and 0.5% severe. Women with 61% showing TMD, as compare to men 73.93%. When considering only severe TMD, only women are affected 0.5%. Participant with any level of TMD show marked characteristics: 12.53% considered themselves tense people; 17.5% reported to clench or grind their teeth; 8.88% reported clicking of the temporomandibular joint; 24.28% reported frequent headache. Conclusion: The result of the study concluded that the TMD a high prevalence among young adult in Karachi, among participant with TMD most of the participants had mild TMD which reveals that in young population about half of the participants presented with mild TMD. Key Points: Temporomandibular disorders (TMDs), Mastication, Helkimo’s indexes, Fonseca anamnestic Index (FAI)